The specifcity of resistance training exercises to swimming performance: a waveform analysis approach - Crowley, E.; Warmenhoven, J.; Harrison, A. J.; Lyons, M. (ISBS Proceedings Archive (Michigan), 2019)
The studies aim was to assess the specificity of dry-land resistance training exercises (RT) to front crawl swimming (FC) using electromyography (EMG) waveform analysis. Fourteen male international and national level swimmers were recruited. EMG data were collected during FC and bench press (BP) and pull up (PU) exercises. 3 x 35 m FC bouts and 3 x 5 repetitions for BP and PU, respectively, one at 70 % and two at 100 % of maximal exertion, with 5 minute inactive recovery between trials. Pearson pointwise correlation identified movement pattern relationships between RT and FC waveforms. The results show that FC and BP only found periods that reached the point wise correlation (r = 0.5) and time series (= 5%) threshold for the tricep brachii and upper trapezius. This series of analysis may aid in developing a metric for quantifying the specificity of RT to athletic performance.